The Role of Chinese Family in the Spread of Christianity in the Seventeenth-Century China. The Xu Family of Shanghai as an Example - Adamek, Piotr (Studia Warmińskie, 2022)
Chinese family played a fundamental role in the spreading of Christianity in China during the Late Ming and Early Qing dynasty (17 century). The contact of the first Jesuit missionaries with Chinese people was usually limited to men, as e.g. Confucian scholars. Some of them, however, converted their families after they became Catholic. These families were a very important basis for the missionary work: they supported missionaries, organized the religious life of the Chinese Church, and evangelized their neighbors. Without Chinese families the Chinese mission would be virtually impossible. A historical review of the role of Chinese family in the spread of Christianity in China in 17th Century will be presented on the example of the Xu Family from Shanghai. The eminent Confucian scholar Xu Guangqi could – after his conversion to Christianity – convert also his whole family. This conversion helped not only to establish Catholic Church in Shanghai but was also crucial in the process of maintaining Christianity as a “family religion.” Based on published sources, the impact of Xu family on the Catholic Church in China will be analyzed and discussed.